There is more to the knee joint than just the quadriceps: A systematic review with meta-analysis and evidence gap map of hamstring strength, flexibility, and morphology in individuals with gradual-onset knee disorders - Lopes, Helder S. [UNESP]; Waiteman, Marina C. [UNESP]; Priore, Liliam B. [UNESP]; Glaviano, Neal R.; Bazett-Jones, David M.; Briani, Ronaldo V. [UNESP]; Azevedo, Fábio M. [UNESP] (Elsevier, 2024)
Background: Impairments in hamstring strength, flexibility, and morphology have been associated with altered knee biomechanics, pain, and function. Determining the presence of these impairments in individuals with gradual-onset knee disorders is important and may indicate targets for assessment and rehabilitation. This systematic review aimed to synthesize the literature to determine the presence of impairments in hamstring strength, flexibility, and morphology in individuals with gradual-onset knee disorders. Methods: Five databases (MEDLINE, Embase, CINAHL, SPORTDiscus, and Web of Science) were searched from inception to September 2022. Only studies comparing hamstring outcomes (e.g., strength, flexibility, and/or morphology) between individuals with gradual-onset knee disorders and their unaffected limbs or pain-free controls were included. Meta-analyses for each knee disorder were performed. Outcome-level certainty was assessed using the Grading of Recommendations Assessment, Development, and Evaluation, and evidence gap maps were created. Results: Seventy-nine studies across 4 different gradual-onset knee disorders (i.e., knee osteoarthritis (OA), patellofemoral pain (PFP), chondromalacia patellae, and patellar tendinopathy) were included. Individuals with knee OA presented with reduced hamstring strength compared to pain-free controls during isometric (standard mean difference (SMD) = –0.76, 95% confidence interval (95%CI) : –1.32 to –0.21) and concentric contractions (SMD = –0.97, 95%CI : –1.49 to –0.45). Individuals with PFP presented with reduced hamstring strength compared to pain-free controls during isometric (SMD = –0.48, 95%CI : –0.82 to –0.14), concentric (SMD = –1.07, 95%CI : –2.08 to –0.06), and eccentric contractions (SMD = –0.59, 95%CI : –0.97 to –0.21). No differences were observed in individuals with patellar tendinopathy. Individuals with PFP presented with reduced hamstring flexibility when compared to pain-free controls (SMD = –0.76, 95%CI : –1.15 to –0.36). Evidence gap maps identified insufficient evidence for chondromalacia patellae and hamstring morphology across all gradual-onset knee disorders. Conclusion: Our findings suggest that assessing and targeting impairments in hamstring strength and flexibility during rehabilitation may be recommended for individuals with knee OA or PFP.
Keywords: Chondromalacia patellae; Knee flexors; Knee osteoarthritis; Patellar tendinopathy; Patellofemoral pain